The Influence of Investment, Labor and Inflation on Gross Regional Domestic Product in North Sulawesi Province - Nangka, Bridget Maydeline; Masinambow, Vecky A. J.; Masloman, Irawaty (PT FORMOSA CENDEKIA GLOBAL, 2024)
The gross regional domestic product is one of the most crucial indicators of a region's economic progress. The growth can be impacted by a variety of factors, including increased labor, increased investment, and steady or decreasing inflation. Finding the partial and simultaneous effects of labor, inflation, and investment on North Sulawesi's gross regional product is the aim of this study. Time series secondary data from the Central Bureau of Statistics are used in this study for the years 2008–2022. Multiple linear regression analysis with E-Views 8 was used in this research. The results showed that labor and inflation had positive and significant effects on North Sulawesi's GDP. Investment, on the other hand, had positive but not significant effects. Along with that, labor, investment, and inflation all have a positive and significant effect on North Sulawesi's gross regional domestic product.